2018
DOI: 10.3390/mti2040080
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Framework of Architectural Paradigms for the User-Centered Design of Virtual Environments

Abstract: In some circumstances, immersion in virtual environments with the aid of virtual reality (VR) equipment can create feelings of anxiety in users and be experienced as something “frightening”, “oppressive”, “alienating”, “dehumanizing”, or “dystopian”. Sometimes (e.g., in exposure therapy or VR gaming), a virtual environment is intended to have such psychological impacts on users; however, such effects can also arise unintentionally due to the environment’s poor architectural design. Designers of virtual environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…This VR-based psychoeducational experience has been created following the theoretical framework of architectural approaches for the user-centered design (UCD) of virtual environments developed by Gladden [ 70 ]. Since the scientific literature suggests that naturalistic virtual environments cause a relaxing effect and an increase in positive emotions [ 71 73 ], a small tropical island was chosen as the setting.…”
Section: Methodsmentioning
confidence: 99%
“…This VR-based psychoeducational experience has been created following the theoretical framework of architectural approaches for the user-centered design (UCD) of virtual environments developed by Gladden [ 70 ]. Since the scientific literature suggests that naturalistic virtual environments cause a relaxing effect and an increase in positive emotions [ 71 73 ], a small tropical island was chosen as the setting.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding virtual reality, it has been demonstrated that, by optimizing the virtual environment's architecture, the use of UCD in the development of virtual experiences offers a more efficient, satisfying, user-friendly experience (Gabbard et al, 1999;Jerald, 2015;Barbieri et al, 2018;Gladden, 2018). It has been employed to design and evaluate virtual experiences in museums (Barbieri et al, 2018), tourism (Poux et al, 2020), automotive industries (de Clerk et al, 2019), and military (Hix et al, 1999), and medical fields (Vailland et al, 2019).…”
Section: Development and Evaluation Protocol Of The Mind-vr Psychoeducational Virtual Experiencementioning
confidence: 99%
“…The design of the experience is based on the theoretical framework of architectural paradigms for the UCD of virtual environments developed by Gladden (Gladden, 2018). By considering the unique possibilities for structuring and experiencing space within virtual environments and reinterpreting Norberg-Schulz's schemas in the context of virtual environment design (Norberg-Schulz, 1980), this framework formulated six fundamental architectural paradigms available to designers of virtual environments that could easily be incorporated as an additional step within the UCD process.…”
Section: Selection Of the Architectural Paradigm For The Design Of The Virtual Reality Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…More recent phenomenologically oriented investigations relevant to virtual reality have included analyses of embodiment and intentionality in VR from the perspectives of Merleau-Ponty (Ajana, 2005;Cobián, 2008;McBlane, 2013;Bailey, 2016) and Stein (Fuentes, 2016); Heideggerian explorations of VR focusing on truth, inauthenticity, the world, and aesthetic experience (Coyne, 1994;Polt, 2015;Geng & Peng, 2016); explorations of the connection between the lifeworld and virtual reality (Beeson, 2001;Deuze, 2014;Butnaru, 2015); analyses that relate Ingarden's aesthetics to virtual reality as art and narration (Ryan, 1999(Ryan, , 2001(Ryan, , 2015Drazdauskas, 2006;Vilariño Picos, 2011;Przegalińska, 2014); frameworks for the design of virtual environments that draw on Norberg-Schulz's architectural phenomenology (Gladden, 2018b); broader phenomenological aesthetic analyses of virtual reality (Bekesi, 1999;Rabanus, 2009;Rousseaux, 2010); and more general phenomenological analyses of VR (Kornelsen, 1991;Murray, 1999;Schroeder, 2003;Heinzel & Heinzel, 2010;Asanowicz, 2014). This text seeks to advance such phenomenological study by investigating the nature of the VR-facilitated virtual world qua world and our experience of it.…”
Section: Previous Phenomenological Analyses Of Vrmentioning
confidence: 99%